Making GRADE accessible: a proposal for graphic display of evidence quality assessments. Issue 3 (18th May 2011) - Khan, Khalid S; Borowiack, Ewa; Roos, Carolien; Kowalska, Monika; Zapalska, Anna; Mol, Ben W; Mignini, Luciano; Meads, Catherine; Walczak, Jacek; ,
Abstract : When generating guidelines, quality of evidence is frequently reported in tabulated form capturing several domains, for example, study design, risk of bias and heterogeneity. Increasingly, this is done using the Grading of Recommendations Assessment, Development and Evaluation approach. As assimilating large amount of tabulated data across several comparisons and outcomes spread over many pages (sometimes hundreds) is not easy, there is a need to present evidence summaries in a more effective way. A graphic display plotting the several domains used in evidence grading on equiangular spokes starting from the same point, the data length of each spoke proportional to the magnitude of the quality, succinctly captures tabulated information. These plots allow easy identification of deficiencies, outliers and similarities in evidence quality for individual and multiple comparisons and outcomes, paving the way for their routine use alongside tabulated information.